Original article Apoptotic neuronal changes enhanced by zinc chelator - TPEN in organotypic rat hippocampal cultures exposed to anoxia - Nagańska, Ewa; Matyja, Ewa (Folia Neuropathologica, 2006)
Both, the neurotoxic and neuroprotective effects of zinc have been well established, but the exact mechanism of its dual abilities still remains unclear. It has been shown that zinc deficiency leads to progressive neuronal injury. Therefore a safe zinc concentration levels seem to be necessary in neuronal protection from different noxious factors. This study was undertaken to determine the effect of zinc chelating agent – TPEN on neuronal morphological changes in organotypic hippocampal culture and its effect on post-anoxic changes in this model. The study evidenced that exposition to 15 µM of TPEN induced various stages of apoptotic changes in hippocampal pyramidal neurons and enhanced the anoxia-induced neuronal apoptosis in this model. These results confirmed the hypothesis that manipulations of intracellular pool of zinc by zinc-chelating agents may be a cause of both induction and prevention of apoptotic cell death in various pathological conditions.